METHODS OF HIDING SPACE: SPEEDING AND SIMULATION - Мухина, Е. Н. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2016)
This article deals with a change in the view of the epistemological space in the context of topological turn. The article examines methods of hiding spaces such as the speeding and simulation. Speeding is considered on the basis of the theory of P. Virilio, in the context of which also explores concepts dromology, dromokracy and hronopolitic. In the context of the theory of simulation Baudrillard’s discusses the phenomena of mimesis, abstraction and hyper-reality and virtuality. Both theories are not investigated by the author as to conflict, but are viewed as complementary.